Copper-catalyzed borylamidation of vinyl arenes with isocyanates. Issue 54 (4th June 2020) - Su, Zhenni; Feng, Yunqiu; Zou, Rong; Qiu, Xianfan; Wang, Jian; Tao, Chuanzhou
Abstract : A copper-catalyzed borylative amidation of vinyl arenes with isocyanates and bis(pinacolato)diboron has been developed. Abstract : A copper-catalyzed borylative amidation of vinyl arenes with isocyanates and bis(pinacolato)diboron has been developed. This new protocol, which can be performed on a gram-scale, utilizes isocyanates as simple precursors to provide access to a range of boryl alkyl amides. The products contain valuable amide and boronate, which are amenable for further elaboration, and have versatile synthetic utilities.